Association of oral pre-malignant lesions with the consumption of tobacco - Joshi, Arpita; Jani, Chinmay; Jain, Kushboo; Bala, D. V.; Jetpariya, Divyesh; Jadav, Harshal (International Journal Of Community Medicine And Public Health, 2019)
Background: Tobacco consumption in the form of chewing and smoking is one of the biggest addictions. It causes various oral pre-malignant lesions which mainly include oral sub-mucous fibrosis (OSMF) caused by betel nut consumption and tobacco quid lesion, leukoplakia, erythroplakia and smoker’s palate caused by chewing and smoking tobacco. Methods: The data about the past and present consumption of tobacco was collected from 909 individuals. Based on the tobacco habits, the oral cavity findings were assessed and the statistical analysis was carried out to find the significance of associations observed between tobacco consumption and lesions. Results: Out of 909 subjects, 537 were consuming tobacco, out of which 284 were chewers, 65 were smokers and 76 were consuming in both forms. Out of the 284 tobacco chewers, 43% had oral lesions (19.4% had OSMF and 21.5% had tobacco quid) as compared to just 1% of workers having oral lesions (OSMF) amongst those who had no addiction. There was a high prevalence of lesion in tobacco chewers (p<0.005). Out of total smokers, 15.8% had smoker’s palate whereas no lesion was seen in the non-addicted workers. The odds of developing oral pre-malignant lesion are 43.62 times higher in exposed individuals. Conclusions: The tobacco consumption in any form is hazardous. Betel nut exposure causes more harmful effect which goes unnoticed. Awareness should be created about various lesions caused by tobacco as well as betel nut and special steps should be taken for early diagnosis and its treatment.